The Metal Detectorist Finds from Gjellestad and Surrounding Areas - Margrete Figenschou Simonsen; Christian Løchsen Rødsrud (Viking)
This chapter aims to give an overview of the archaeological finds from metal detecting at Gjellestad and surrounding areas, and to relate these finds to truncated archaeological structures recorded by the project’s extensive ground penetrating radar survey. Can areas with special functions like trade and handicrafts be identified? Furthermore, the study explores what kinds of kind of networks the finds represent and if is it possible to confirm areas with special functions like trade and handicrafts. The artefact material consists of 87 different objects, with a predominance of late Iron Age and later finds. The provenance for the metal finds can be traced to the Baltic and East Scandinavia, the British Isles, Central Asia and the Middle East. Spatially they cluster in three areas; an area with artefacts relating to daily use as well as weighing and handling valuables above settlement traces to the north; an area between today’s farmhouses and the Jell mound (Jellhaug) with ploughed up artefacts from burials; and to the south, near the Viking Age shoreline, is an area with artefacts connected to trade.